Simulating the effect of high column density absorbers on the one-dimensional Lyman α forest flux power spectrum. Issue 3 (15th November 2017) - Rogers, Keir K; Bird, Simeon; Peiris, Hiranya V; Pontzen, Andrew; Font-Ribera, Andreu; Leistedt, Boris
Abstract: We measure the effect of high column density absorbing systems of neutral hydrogen (H i ) on the one-dimensional (1D) Lyman α forest flux power spectrum using cosmological hydrodynamical simulations from the Illustris project. High column density absorbers (which we define to be those with H i column densities N(H I) > 1.6 × 10^17 atoms cm^-2 ) cause broadened absorption lines with characteristic damping wings. These damping wings bias the 1D Lyman α forest flux power spectrum by causing absorption in quasar spectra away from the location of the absorber itself. We investigate the effect of high column density absorbers on the Lyman α forest using hydrodynamical simulations for the first time. We provide templates as a function of column density and redshift, allowing the flexibility to accurately model residual contamination, i.e. if an analysis selectively clips out the largest damping wings. This flexibility will improve cosmological parameter estimation, for example, allowing more accurate measurement of the shape of the power spectrum, with implications for cosmological models containing massive neutrinos or a running of the spectral index. We provide fitting functions to reproduce these results so that they can be incorporated straightforwardly into a data analysis pipeline.